Gambaran Pengetahuan Sikap dan Perilaku Masyarakat Tentang Penggunaan Garam Beryodium Pada Anggota Keluarga di Wilayah Kerja Puskesmas Gentungan Kecamatan Bajeng Barat Kabupaten Gowa - Ayu Astuti; Sartika Sartika; Andi Budiyanto Adi Putra; Asriani Bahar (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Iodine deficiency disorder (IDD) is a set of symptoms caused by iodine deficiency in the body over a long period of time. Iodine deficiency disorder is still a public health problem in more than 50 countries. Iodine is beneficial for normal growth, preventing goiter, maintaining healthy skin, teeth and hair. This study aims to determine the description of knowledge, attitudes and behavior of the community about the use of iodized salt in family members in the Gentungan Health Center Working Area, West Bajeng District, Gowa Regency. The type of research used was descriptive quantitative research with a cross-sectional study design. The sample was obtained by Accidental Sampling with a total of 35 respondents from 125 families of the total population. The instruments used in this study were questionnaire sheets and iodine tests for data collection. This study showed that as many as 16 respondents (45.7%) had sufficient knowledge about the use of iodized salt, as many as 24 respondents (68.6%) had a positive and supportive attitude towards the use of iodized salt, as many as 29 respondents (82.9%) had good behavior towards the use of iodized salt. This study concludes that most of the people in the Gentungan Health Center Working Area almost entirely already use iodized salt as daily consumption and already have quite good knowledge, attitudes and behavior towards the consumption of iodized salt, but there are still a small number of respondents who do not understand how to use iodized salt properly. It is expected for health workers to increase health promotion about iodized salt to the community, not only the recommendation to use iodized salt but also other detailed information such as how to use salt properly.